Evaluating the longitudinal physical and psychological health effects of persistent long Covid 3.5 years after infection - Gregory Vallée; David Xi; Gordana Avramovic; Brendan O’Kelly; John S. Lambert (PLoS ONE, 2025)
This is a 3.5-year single-center observational cohort study investigating the longitudinal impact of Long Covid on the physical and mental health of patients. Patients were assessed at 3 months, 1 year, and 3.5-years post-infection using the 12-item Short Form Survey, Patient Health Questionnaire-9, Generalized Anxiety Disorder-7 scale and the Impact of Events Scale-Revised questionnaire. Additionally, a clinical symptom review was conducted for patients with persistent Long Covid at the 3.5-year follow-up. We had 149 respondents at 3 months, 94 at 1 year and 85 at 3.5-year. Of those who participated, 72% had Long Covid at the 3-month follow-up, with 26% and 25% having persistence of Long Covid symptoms at 1-year and 3.5 years, respectively. The most reported symptoms at the 3.5-year timepoint included fatigue, difficulty sleeping and easy crashing following activities. Overall, patients’ Physical Composite Scores significantly improved between the 3-month and 3.5-year timepoints. However, the Physical Composite Scores of patients with persistent Long Covid were significantly lower than those of non-Long Covid patients at both the 3-month and 1-year follow-ups. The Mental Composite Score of persistent Long Covid patients remained significantly lower than individuals without Long Covid at all timepoints. At 3 months, Long Covid disproportionately met the criteria for depression, anxiety and PTSD symptoms. At 1 and 3.5 years, patients with persistent Long Covid were more likely to meet the criteria for depressive symptoms than those without Long Covid. Between the 3-months and 3.5-year timepoints, there was a significant reduction in the number of patients with persistent Long Covid who met the criteria for PTSD and anxiety symptoms. Although patients with Long Covid for 3.5 years had shown improvements in both their physical and mental health over time, they continue to lag behind those without Long Covid.